Marketing Channel Analyst - Anggraeni, Andi Sri (Journal Development Manecos, 2023)
This article discusses the analysis of the marketing channels involved in the process of making a product or service ready for use or consumption. This article aims to know and understand the meaning of the marketing channel, know the function of the marketing channel, know the levels that exist in the marketing channel and know how to make decisions in the marketing channel.